MODEL OF SPECIALIST AS REPRESENTATION OF THE TRAINING PROCESS PURPOSE IN THE AUTOMATED PEDAGOGICAL DIAGNOSTICS SYSTEM - Kolgatin О.Г. (Journal of Information Technologies in Education (ITE), 2010)
Approaches to design of the pedagogical model of specialist are analyzed with special attention to models of competence. Specific demands to such models in the automated pedagogical diagnostics system are underlined, and the system of parameters, which describe the expectant knowledge, skills and competence components of the student – future specialist, is suggested.